Accumulation and Self-Cleaning of PSP Toxins in Green Mussel, Perna viridis, Fed on Various Cell Density of Alexandrium minutum - Phumphoung, Patiphan; Lirdwitayaprasit, Thaithaworn; Subsinserm, Supanoi (Journal of Fisheries and Environment, 2025)
Paralytic shellfish poisoning (PSP) is a serious threat to marine ecosystems and human health, caused by toxins from harmful algal blooms. This study investigates the accumulation and self-cleaning processes of PSP toxins in the green mussel, Perna viridis, fed various cell densities of Alexandrium minutum, a major PSP toxin producer. The first part assessed the clearance rate of the green mussels over 24 h, feeding them A. minutum at concentrations of 100, 500, 1,000, and 3,000 cells·mL-1. Results showed that clearance rates increased with higher cell density. The total PSP toxins accumulated in the mussels were proportional to the total toxin found in A. minutum. The second part of the study examined the accumulation of PSP in mussels fed A. minutum for two consecutive weeks at a cell density of 500 cells·mL-1, followed by two weeks of self-cleaning while being fed the non-toxic alga Isochrysis sp. The results showed that the PSP toxin content increased during feeding on A. minutum, surpassing the regulatory limit (0.8 µgSTXeq·g-1) after 10 days. PSP toxin levels peaked at 2.16±0.21 µgSTXeq·g-1 after 14 days, approximately 2.7 times the regulatory limit. During the self-cleaning period, toxin levels gradually declined to safe concentrations within one day, with no detectable toxins at the end of the experiment. The elimination of GTX1,4 toxin (highly toxic derivatives) was particularly rapid during the self-cleaning phase. These findings suggest that mussels could serve as an effective indicator species for early warning of PSP outbreaks.